Performance Assessment of Reinforced Concrete Frame under Close-In Blast Loading - Solomon Abebe; Tesfaye Alemu Mohammed (Advances in Civil Engineering)
The need for assessing and retrofitting structures increased with time as terrorism-induced explosion trends rose with time. This paper presents a numerical investigation on performance assessment of a two-story, one-bay seismic resistant reinforced concrete framed building under close-in blast loading. ANSYS AUTODYN, an explicit nonlinear finite element software program, was used for 3D model development and analysis. The experimental results reported in the literature were used to validate proposed FE models. Furthermore, parametric studies on close-in explosive story-to-story locations and charge masses were performed on both conventional and seismically detailed RC framed structures. FEA results showed that a decrease in scaled distance raised effective plastic strain and damage index values. Furthermore, simultaneous use of close-spaced transverse steel reinforcement spacing in mid-height and ends of reinforced concrete columns is found to be effective in reducing both effective plastic strains and damage index values.